2021
DOI: 10.3390/su13073979
|View full text |Cite
|
Sign up to set email alerts
|

Effects after 1500 Hardening Days on the Microstructure and Durability-Related Parameters of Mortars Produced by the Incorporation of Waste Glass Powder as a Clinker Replacement

Abstract: One of the ways of lessening the CO2 emissions of cement industry consists of replacing clinkers with supplementary cementitious materials. The required service life of real construction elements is long, so it is useful to characterize the performance of these materials in the very long term. Here, the influence of incorporating waste glass powder as a supplementary cementitious material, regarding the microstructure and durability of mortars after 1500 hardening days (approximately 4 years), compared with re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 36 publications
(54 reference statements)
1
4
0
Order By: Relevance
“…The solid phases formed as products of these reactions, would progressively close the pores, giving as a result lower porosity values, as has been observed. The result that additions with pozzolanic activity, such as fly ash and glass powder, did not produce a noticeable reduction of total porosity of cement‐based materials, compared to reference mortars without additions, whereas they produced a significant pore refinement, would agree with the results pointed out by other authors 22,41 . However, the binder with slag and brick powder (S‐BP series) reached similar total porosity values at 250 days than reference specimens, which could be explained in relation to the hydraulic activity of slag, which would have a more notable effect in the reduction of porosity, according to other works 22,53 …”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The solid phases formed as products of these reactions, would progressively close the pores, giving as a result lower porosity values, as has been observed. The result that additions with pozzolanic activity, such as fly ash and glass powder, did not produce a noticeable reduction of total porosity of cement‐based materials, compared to reference mortars without additions, whereas they produced a significant pore refinement, would agree with the results pointed out by other authors 22,41 . However, the binder with slag and brick powder (S‐BP series) reached similar total porosity values at 250 days than reference specimens, which could be explained in relation to the hydraulic activity of slag, which would have a more notable effect in the reduction of porosity, according to other works 22,53 …”
Section: Discussionsupporting
confidence: 89%
“…The result that additions with pozzolanic activity, such as fly ash and glass powder, did not produce a noticeable reduction of total porosity of cement-based materials, compared to reference mortars without additions, whereas they produced a significant pore refinement, would agree with the results pointed out by other authors. 22,41 However, the binder with slag and brick powder (S-BP series) reached similar total porosity values at 250 days than reference specimens, which could be explained in relation to the hydraulic activity of slag, which would have a more notable effect in the reduction of porosity, according to other works. 22,53 The electrical resistivity is a useful parameter for obtaining information related to the connectivity of pores, as well as the evolution of the microstructure.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Among them, the use of eco-friendly cements with additions substituting clinker is becoming more and more common [ 6 , 7 , 8 ]. Most of these additions or supplementary cementitious materials are obtained from wastes generated in other industries [ 9 , 10 , 11 , 12 ], so the reuse of these wastes in cement manufacture would avoid other environmental impacts, also contributing to sustainability. In addition, it has been reported that the use of some of these additions produces an enhancement in the behavior of cementitious materials [ 10 , 13 , 14 ], so the study of their effects still constitutes a relevant area of investigation.…”
Section: Introductionmentioning
confidence: 99%